2012
DOI: 10.1111/j.1467-7652.2012.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Mice fed on a diet enriched with genetically engineered multivitamin corn show no sub‐acute toxic effects and no sub‐chronic toxicity

Abstract: SummaryMultivitamin corn is a novel genetically engineered variety that simultaneously produces high levels of b-carotene, ascorbate and folate, and therefore has the potential to address simultaneously multiple micronutrient deficiencies caused by the lack of vitamins A, B9 and C in developing country populations. As part of the development process for genetically engineered crops and following European Food Safety Authority (EFSA) recommendations, multivitamin corn must be tested in whole food ⁄ feed sub-chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(46 reference statements)
1
6
0
1
Order By: Relevance
“…No indications of toxicity were evident compared with animals fed on control diets. The study thus confirmed that diets enriched with 'multivitamin corn' did not have any adverse effects on mice, did not induce any clinical signs of toxicity and did not contain known allergens (61) .…”
Section: Hypervitaminosissupporting
confidence: 68%
“…No indications of toxicity were evident compared with animals fed on control diets. The study thus confirmed that diets enriched with 'multivitamin corn' did not have any adverse effects on mice, did not induce any clinical signs of toxicity and did not contain known allergens (61) .…”
Section: Hypervitaminosissupporting
confidence: 68%
“…However, it has been severely criticized by some scientists:it emphasizes chemical composition at the expense of biological, toxicological, and immunological tests; it is not clear what level of similarity can make the GM and non-GM food substantially equivalent (Bhattacharya et al 2013) or it does not define the point at which a food is no longer substantially equivalent (Picone et al 2011). Subchronic rodent toxicology studies have been conducted with whole grains and processed feed fractions obtained from numerous GM crops in accordance with guidelines of repeated dose 90-day oral toxicity study in rodents (Cao et al 2011;Yuan et al 2011;Arjó et al 2012;Liu et al 2012;Tang et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…There were no significant differences in any of the production traits that were monitored during the trial (live weight, feed intake, average weight gain or feed conversion rate) agreeing with the 90-day exposure experiment in mice (Arjó et al, 2012). At 190 days, the pigs were slaughtered and samples of liver, subcutaneous fat and muscle (longissimus dorsi and gluteus medius) were collected to determine the fat content and composition.…”
Section: Swine Productionmentioning
confidence: 82%
“…Similarly, there were no significant differences between the diet groups in terms of clinical observations, hematological parameters, biochemical markers and absolute or relative changes in organ weight. In summary, Carolight® was found to be compositionally substantially equivalent to M37W and to satisfy current requirements to demonstrate the absence of sub-chronic toxicity (Arjó et al, 2012). No single animal model addresses all potential sources of toxicity (Gephart et al, 2001) but a positive outcome following a 90-day sub-chronic toxicity test provides strong supporting evidence for safety (Ricroch, 2013).…”
Section: Animal Feeding Trials As a First Step Towards A Human Nutritmentioning
confidence: 83%
See 1 more Smart Citation